Risk management of logistic department of electricity company - Hasda, Erdiyan Krisnadi; Sumirat, Erman (Faculty of Economics and Business Mulawarman University, 2018)
This study is conducted to carry out the risk management process in the logistics department of the electricity company unit, which has the main duties in managing electricity transmission assets, controlling investment and logistics transmission, and maintaining transmission assets. The risk management process in this study was prepared as a step in shaping the risk profile of business processes in the logistics field to avoid the failure of business processes that resulted in unavailbility of logistics material, which could impact the electricity transmission. This study uses the AS/NZS ISO 31000:2009 Risk Management Standard framework. Calculation of risk priorities is using Analytical Hierarchy Process, based on a questionnaire to experts in the field of company logistics. From the calculation using AHP, Work Accident (HR2) has been identified as the most vulnerable risk among others risk factors.